Effect of indium as a surfactant in (Ga1−xInx)2O3 epitaxial growth on β-Ga2O3 by metal organic vapour phase epitaxy. (19th January 2015) - Baldini, M; Albrecht, M; Gogova, D; Schewski, R; Wagner, G
Abstract: (Ga1− x In x )2 O3 epitaxial layers have been grown on (100) β -Ga2 O3 substrates by metal organic vapour phase epitaxy (MOVPE). The process parameters were tuned in order to obtain an In-poor (Ga1− x In x )2 O3 alloy, limiting the In incorporation below 3%. In this way it was possible to study the effect of In on the growth dynamics of Ga2 O3 . By varying the flow of the carrier gas (Ar) through the In precursor (trimethylindium) in a wide range, it was observed that for Ar/TMIn flows higher than a minimum threshold value, In was essential to obtain layers with very high crystal quality. The concentration of structural defects, such as stacking faults and twins, decreased dramatically and step-flow growth mode was achieved. These results have been explained by the tendency of In to float on the growing Ga2 O3 surface, delivering an effective surfactant effect.